Preserving Meaning and Context: A Study of Cultural Adaptation in the Translation of Arabic Proverbs - Zaki Ghufron; Subhan Subhan; Mufrodi Mufrodi; Azizah Alawiyyah (ALSINATUNA, 2023)
This research delves into the intricate dynamics of translating proverbs, aiming to ensure that the essence of the source language is accurately conveyed in the target language. Translating proverbs presents unique challenges due to the inherent cultural and contextual nuances embedded within them. To address this, employing culturally equivalent strategies becomes crucial in faithfully representing the intended meaning. The process of translating through culture is not merely a mechanical task; it serves as a bridge fostering a profound understanding between different cultures. This bridge facilitates the effective communication of proverbial messages in the target language, exemplified by the proverb "Qabla ar-rima tumlau al-kanain." A literal translation fails to capture its essence, but a cultural approach reveals its Indonesian equivalent: "sedia paying sebelum hujan." This stark contrast underscores the necessity of cultural adaptation to convey the intended message accurately. This qualitative study relies on data sourced from various references, such as "Al-Balaghah Al-Wadhihah" and "Al-Amtsal Al-Arabiyyah Wa Al-Amtsal Al-Amiyah: Muqaranah Dalaliyah" by Al-hamzawi. Proverbs are extracted, and the research applies content analysis and a cultural adaptation approach. The fusion of Arabic proverbs with Indonesian counterparts from works like Dipo Udi's "Kumpulan Peribahasa Indonesia" and the Indonesian Ministry of Education and Culture's "500 Pepatah" allows for a comprehensive analysis. The findings affirm that cultural adaptation effectively conveys proverbial messages. This adaptation involves substituting proverbs with culturally relevant expressions, ensuring a seamless integration into the cultural context of the target language. Ultimately, this research sheds light on the significance of cultural sensitivity in translating proverbs for a more nuanced and accurate representation of their intended meanings.